The prevalence and risk factors for human Brucella species infection in a cross-sectional survey of a rural population in Punjab, India. (22nd February 2020) - Mangtani, Punam; Berry, Isha; Beauvais, Wendy; Holt, Hannah R; Kulashri, Amit; Bharti, Satinder; Sagar, Vivek; Nguipdop-Djomo, Patrick; Bedi, Jasbir; Kaur, Manmeet; Guitian, Javier; McGiven, John; et al.
Abstract: Background: Brucellosis is an important neglected zoonosis. Effective cattle vaccines are available but are infrequently used in India, where rural households commonly own one or two cattle as sources of protein and income. We assessed the prevalence of infection and risk factors in humans. Methods: We conducted a cross-sectional sero-survey in randomly selected individuals in 60 villages in Punjab. Infection prevalence was assessed by positive Rose Bengal testing or immunoglobulin G enzyme-linked immunosorbent assay. Risk factors were adjusted for potential confounding using multivariable analyses. Results: Of the 1927 subjects who were approached, 93% agreed to participate. Age-standardised prevalence for Brucella infection was 2.24% (95% confidence interval [CI] 1.61 to 3.11). More than 60% of households kept cattle and 10% assisted with calving or abortions. Nearly all individuals consumed boiled cow/buffalo milk from their own or neighbours' cattle and 3.3% consumed goat's milk. There was a 2.18 times increased odds (95% CI 0.96 to 4.95) of infection with calving/abortions and a 4.26 times increased odds (95% CI 1.33 to 13.6) with goat's milk but not bovine milk consumption. Conclusions: An association with calving/abortions and goat's milk consumption was seen. Brucella vaccination of household livestock would reduce the risk to humans in such settings. Additional measures include biosecurity training around calving/abortions, education to boil all milk and for healthcare workers to test for brucellosis.